A Fully Phosphane‐Substituted Disilene. Issue 20 (12th April 2017) - Izod, Keith; Evans, Peter; Waddell, Paul G.
Abstract: There is growing interest in compounds containing functionalized E=E multiple bonds (E=Si, Ge, Sn, Pb) because of their potential to exhibit novel physical and chemical properties. However, compounds containing multiple functionalizations are rare, with scarcity increasing with increasing degree of substitution. The first ditetrelene R2 E=ER2 in which the E=E bond is substituted by four heteroatoms (other than Si) is described. The tetraphosphadisilene {(Mes)2 P}2 Si=Si{P(Mes)2 }2 (7 ) is readily isolated from the reaction between SiBr4 and [(Mes)2 P]Li, the latter of which acts as a sacrificial reducing agent. The structure of7 is presented, while the bonding in, and stability of7 were probed using DFT calculations. Abstract : The tetraphosphadisilene compound {(Mes)2 P}2 Si=Si{P(Mes)2 }2 is a readily accessible complex that is stable in the solid state, and is unlike tetraaminodisilenes (R2 N)2 Si=Si(NR2 )2, which are typically unstable with respect to their silylene monomers (R2 N)2 Si. Tetraphosphadisilene is the first structurally characterized example of a ditetrelene substituted by more than two heteroatoms other than silicon.